Intrauterine exposure to HBsAg attenuates the immune response to hepatitis B vaccine via the miR-155-5p/MyD88 axis of DCs in mouse pups - Xufeng Cui; Jia Lian; Yangle Sun; Xiaosheng Zhang; Bihong Ke; Xinyuan Mo; Ying Zhang; Tian Yao; Yandi Li; Linying gao; Keke wang; Suping Wang; et al. (Medical Microbiology and Immunology, 2026)

Asymmetric ceramic membranes fabricated using equal amounts of red mud and fly ash for oil-in-water emulsion separation - Rui Zhang; Wenjuan Chen; Siqi Lan; Hongsen Lv; Yali Wang; Qunyan Li; Suping Cui; Qi Wei; Zuoren Nie (Journal of Environmental Chemical Engineering, 2026)

Synergistic regulation mechanism of WO3 on the resistance to thallium poisoned V2O5/TiO2 SCR catalysts - Lingqin Meng; Lu Wei; Duan Zhang; Jialong Wang; Yali Wang; Suping Cui (Chemical Engineering Journal, 2026)

Separate grinding of siliceous materials in cement raw materials: improving burnability and reducing energy consumption - Xin Du; Wenhai Nie; Minghao Liu; Suping Cui; Ruizhi Zhang; Yali Wang; Junlei Ma; Wei Wang (Innovative Infrastructure Solutions, 2026)

CO2-absorbed diethanolamine in cement: Strength development regulated by in-situ carbonation - Hui Liu; Chao Yuan; Jianfeng Wang; Tongsheng Zhang; Binjie Zhou; Penghao Xin; Suping Cui (Journal of Environmental Chemical Engineering, 2026)

Comparison of allocation methods in the life cycle assessment of nickel products - Duan Zhang; Boxue Sun; Suping Cui; Lingqin Meng; Shiwei Du; Zuoren Nie (Journal of Environmental Management, 2026)

Effect of alkanolamine molecular structure on the complexation activation of steel slag: A mechanistic study - Jianfeng Wang; Jiaqi Zhao; Hao Wan; Binjie Zhou; Hui Liu; Jihui Zhao; Suping Cui (Journal of Cleaner Production, 2026)

L1-Norm Multi-Constraint AVO Inversion Based on N-ADMM with an adaptive penalty - Yu Wang; Suping Peng; Yongxu Lu; Xiaoqin Cui; Dong Li; Zihe Xu; Yaoquan Hu; Di Yao (Acta Geophysica, 2026)

Corrigendum to “Enhanced immobilization of heavy metals in cement using functionalized chitosan: Leaching reduction and performance improvement” [J. Clean. Prod. 546 (2026) 147789] - Feng Zhang; Lu Yu; Suping Cui; Yali Wang; Lingqin Meng (Journal of Cleaner Production, 2026)

Activating the hydration activity of steel slag via the chelation of BES-Na for waste resource utilization - Lei Chang; Jianfeng Wang; Suping Cui; Hui Liu; Binjie Zhou; Qiang Cui (Chemical Engineering Journal, 2026)

Exergy-based resource efficiency evaluation of NdFeB magnet production and recycling in China - Duan Zhang; Boxue Sun; Suping Cui; Lingqin Meng; Shiwei Du; Zuoren Nie (The International Journal of Life Cycle Assessment, 2026)

Recycling steel slag waste into Portland cement: Hydration, microstructure and properties in the presence of ligand activators - Lei Chang; Yajing Fang; Suping Cui; Jianfeng Wang; Hui Liu; Binjie Zhou; Qiang Cui (Process Safety and Environmental Protection, 2026)

Holocene vegetation dynamics and anthropogenic imprints in the Chinese Loess Plateau: Insights from pollen records - Zeyu Liu; Yajie Dong; Suping Peng; Anning Cui; Xian Li (Quaternary Science Reviews, 2026)

Enhanced immobilization of heavy metals in cement using functionalized chitosan: Leaching reduction and performance improvement - Feng Zhang; Lu Yu; Suping Cui; Yali Wang; Lingqin Meng (Journal of Cleaner Production, 2026)

Seismic Fault Detection Using Interpretable Tree-Based Ensemble Models with Bayesian Optimization - Yang Li; Suping Peng; Xiaoqin Cui; Peng Lin; Dong Li; Tao He; Kunheng Li; Henggao Geng; Hongpeng Zhao (Pure and Applied Geophysics, 2026)

New strategies for synergistic inhibition of mild steel corrosion by dual-functionalized chitosan: Film formation and Fe2+ adsorption - Minghui Jiang; Xiao Liu; Yurui Xu; Shiyu Li; Xingxin Hu; Xinxin Li; Lei Lu; Ziming Wang; Suping Cui (Journal of Cleaner Production, 2026)

Enhancing the hydration activity of steel slag-Portland cement composite by BES sodium activator - Lei Chang; Suping Cui; Jianfeng Wang; Hui Liu; Binjie Zhou (Sustainable Chemistry and Pharmacy, 2025)

Novel eco-friendly inhibitor for mild steel in simulated concrete pore solution: Experimental and theoretical analysis - Minghui Jiang; Xiao Liu; Xingxin Hu; Shiyu Li; Yurui Xu; Xinxin Li; Lei Lu; Chunlei Xia; Xiangju Liu; Ziming Wang; Suping Cui (Chemical Engineering Journal, 2025)

Post-stack seismic impedance inversion based on sparse-coded Mamba seismic model - Yijian Lin; Suping Peng; Xiaoqin Cui; Yongxu Lu (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Enhanced autotrophic denitrification under salinity stress by bioaugmentation of Sulfurimonas: performance evaluation, microbial community and response mechanisms - Liang Cui; Shasha Wang; Xiaxing Cao; Shicheng Chen; Jiannan Wang; Zhen Chen; Lijing Jiang; Xuezhe Wen; Wanpeng Wang; Qianqian Wang; Zhou Zhou; Suping Yang; et al. (Bioresource Technology, 2025)

A facile strategy to make expanded graphite granules recyclable in oil-water separation via incorporating them into the framework of monolithic cellulose nanofibril aerogels - Siyu Liu; Wenjuan Chen; Yali Wang; Chunsheng Liu; Suping Cui; Qunyan Li; Zuoren Nie; Qi Wei (Journal of Environmental Chemical Engineering, 2025)

MSTC: a unified encoding method for geophysical big data retrieval - Henggao Geng; Suping Peng; Tao He; Na Xu; Zhangang Wang; Xianlei Xu; Xiaoqin Cui; Wenfeng Du; Yang Li; Kunheng Li (Earth Science Informatics, 2025)

Prestack inversion with lateral data difference constraints - Zihe Xu; Suping Peng; Xiaoqin Cui; Yongxu Lu; Peng Lin; Dongshuang Hou (Acta Geophysica, 2025)

Intensified human activities-ecology interaction in the Chinese Loess Plateau at least two millennia: Evidence from palynological analysis - Zeyu Liu; Yajie Dong; Suping Peng; Anning Cui; Xian Li (Review of Palaeobotany and Palynology, 2025)

Simultaneous removal of heavy metals and inorganic nitrogen by using the biofilm of Marichromatium gracile YL28 - Liang Cui; Shicheng Chen; Xiaxing Cao; Xiaobo Zhang; Xiaoping Huang; Tomoyuki Shibata; Yi Yang; Luyao Shi; Chungui Zhao; Shasha Wang; Suping Yang (World Journal of Microbiology and Biotechnology, 2025)

Hydration characteristics of steel slag in the presence of diethanol-isopropanolamine - Lei Chang; Jianfeng Wang; Suping Cui; Yali Wang; Hui Liu; Tianrui Pei; Ziqiang Li (Journal of Cleaner Production, 2024)

The influence of organic components in sludge on selective non-catalytic reduction denitrification - Yali Wang; Xiaotong Zong; Yihui Song; Suping Cui (Environmental Science and Pollution Research, 2023)

Mode of innovative green production for concrete engineering: life cycle assessment of accelerators prepared from aluminum mud wastes - Xiao Liu; Hui Xie; Qifeng Luo; Kun Yang; Chunlei Xia; Jianan Guan; Wu Zhou; Boxue Sun; Ziming Wang; Suping Cui (Environmental Science and Pollution Research, 2023)

An advanced instantaneous frequency method for ground-penetrating radar cavity detection - Tao He; Suping Peng; Xiaoqin Cui; Youwei Zheng; Zhaoyang Shi (Journal of Applied Geophysics, 2023)

Coalbed methane desorption characteristics controlled by coalification and its implication on gas co-production from multiple coal seams - Bin Zhang; Yafei Zhang; Suping Zhao; Wei He; Shu Tao; Zhejun Pan; Yi Cui (Frontiers of Earth Science, 2023)

Development of chemical admixtures for green and environmentally friendly concrete: A review - Guanghong Lai; Xiao Liu; Shiyu Li; Yurui Xu; Yunsheng Zheng; Jianan Guan; Ruijun Gao; Zhongyuan Wei; Ziming Wang; Suping Cui (Journal of Cleaner Production, 2023)

Dual tolerance of ageratum (Ageratum conyzoides L.) to combined pollution of acid and cadmium: Field survey and pot experiment - Zhongzhen Wang; Hongbin Wang; Haijuan Wang; Yongrong Qin; Suping Cui; Guanghui Wang (Journal of Environmental Management, 2023)

Study on the mechanism of iron-rich coal gasification slag on NO conversion in high temperature flue gas of cement kiln - Wang Yali; Han Xiaoning; Cui Suping; Hu Xibo; Ma Xiaoyu; Hao Liwei (Fuel, 2023)

Prestack AVO Inversion of Exact Zoeppritz Equation Using Adaptive Edge Preserving Filter - Zihe Xu; Yongxu Lu; Suping Peng; Xiaoqin Cui; Jin Liao; Haolei Shi (Pure and Applied Geophysics, 2023)

Diffraction enhancement using the double sparse dictionary method - Tao Wang; Suping Peng; Peng Lin; Xiaoqin Cui; Jiawei Zhou (Acta Geophysica, 2022)

A comprehensive assessment of heavy metal(loid) contamination in leafy vegetables grown in two mining areas in Yunnan, China—a focus on bioaccumulation of cadmium in Malabar spinach - Suping Cui; Zhongzhen Wang; Xingjian Li; Hongbin Wang; Haijuan Wang; Wenjie Chen (Environmental Science and Pollution Research, 2022)

A ratiometric fluorescent nanoprobe for ultrafast imaging of peroxynitrite in living cells - Yijing Cui; Suping Han; Jingjing Zhang; Xiaoqing Wang (JBIC Journal of Biological Inorganic Chemistry, 2022)

Time-Lapse Seismic Inversion for Predicting Reservoir Parameters Based on a Two-Stage Dual Network - Dong Li; Suping Peng; Yinling Guo; Yongxu Lu; Xiaoqin Cui; Wenfeng Du (Pure and Applied Geophysics, 2022)

Finite Difference Scheme Based on the Lebedev Grid for Seismic Wave Propagation in Fractured Media - Kang Wang; Suping Peng; Yongxu Lu; Xiaoqin Cui (Pure and Applied Geophysics, 2022)

Plane-Wave Destruction-Based Workflow for Prestack Diffraction Separation in the Shot Domain - Peng Lin; Suping Peng; Xingguo Huang; Yang Xiang; Chuangjian Li; Xiaoqin Cui (Pure and Applied Geophysics, 2022)

Identifying Discontinuities by Extracting Diffractivity from Migrated Seismic Profiles - Chuangjian Li; Suping Peng; Xiaoqin Cui; Peng Lin (Pure and Applied Geophysics, 2022)

Imaging Diffractions Using a Double-Order Weight Function - Chuangjian Li; Suping Peng; Peng Lin; Xiaoqin Cui; Qiannan Liu (Pure and Applied Geophysics, 2022)

A Robust Adaptive Rank-Reduction Method for 3D Diffraction Separation and Imaging - Peng Lin; Jingtao Zhao; Suping Peng; Xiaoqin Cui; Chuangjian Li; Dongjing Xu (Pure and Applied Geophysics, 2021)

Exergy-based resource consumption analysis of cement clinker production using natural mineral and using calcium carbide sludge (CCS) as raw material in China - Boxue Sun; Yu Liu; Zuoren Nie; Feng Gao; Zhihong Wang; Suping Cui (The International Journal of Life Cycle Assessment, 2020)

Anti-Hepatoma Activity of a Novel Compound Glaucocalyxin H In Vivo and In Vitro - Guangfan Hai; Chong Zhang; Yanlong Jia; Suping Bai; Jinfen Han; Lanqing Guo; Taizhen Cui; Bingxuan Niu; Feng Huang; Yu Song (AAPS PharmSciTech, 2015)

The LCA of portland cement production in China - Chen Li; Suping Cui; Zuoren Nie; Xianzheng Gong; Zhihong Wang; Norihiro Itsubo (The International Journal of Life Cycle Assessment, 2015)

Life Cycle Energy Consumption and Carbon Dioxide Emission of Residential Building Designs in Beijing - Xianzheng Gong; Zuoren Nie; Zhihong Wang; Suping Cui; Feng Gao; Tieyong Zuo (Journal of Industrial Ecology, 2012)
Summary This study is based on the three types of residential buildings with framework structures in Beijing: concrete framework construction (CFC), light‐gauge steel framework construction (SFC), and wood framework construction (WFC). The analysis of the environmental load across the life cycle of the three types of buildings is conducted using life cycle assessment (LCA) according to the protocols of the International Organization for Standardization (ISO) 14040/44. The functional unit is the three material building designs, which possess the same function and design plan, and are built in concrete, light‐gauge steel, and light frame wood, inclusive of their respective envelope materials. Throughout the investigation, the calculations of the environmental load data of materials, energy consumption, and carbon dioxide (CO 2 ) emissions are comprehensively assessed and compared. The study shows that over the life cycle, the energy consumption of CFC is almost the same as that of SFC, and each of them is approximately 30% higher than that of WFC. Building use, steel material production, cement production, gypsum board production, and material transport are the main construction activities related to the energy consumption; the net CO 2 emission of CFC is 44% higher than that of SFC and 49% higher than that of WFC. The main source of CO 2 emission is the use of electricity; its contributions to the net CO 2 emissions of WFC, SFC, and CFC are 67%, 64%, and 44%, respectively. The net CO 2 emissions in the transport category cannot be ignored, with proportions amounting to 8%, 12%, and 11% for WFC, SFC, and CFC, respectively.

Cloning and characterization of a wheat β-1,3-glucanase gene induced by the stripe rust pathogen Puccinia striiformis f. sp. tritici - Bo Liu; Xiaodan Xue; Suping Cui; Xiaoyu Zhang; Qingmei Han; Lin Zhu; Xiaofei Liang; Xiaojie Wang; Lili Huang; Xianming Chen; Zhensheng Kang (Molecular Biology Reports, 2010)